The role of phasic norepinephrine modulations during task switching: evidence for specific effects in parietal areas - Wolff, Nicole; Mückschel, Moritz; Ziemssen, Tjalf; Beste, Christian (Brain structure & function, 2018)
Cognitive flexibility is a major requirement for successful goal-directed behavior and their neurobiological underpinnings are becoming better understood. However, the role of the norepinephrine system during task switching is largely enigmatic, despite neurobiological considerations make it likely that the norepinephrine system likely plays an important role. Theoretical considerations also suggest that the norepinephrine system mainly modulates task-switching processes when these rely upon working memory mechanisms. This topic was examined in the current system neurophysiological study integrating event-related potential (ERP) with pupil diameter data as a proximate the norepinephrine system activity. Combined with source localization methods, human brain structure, brain function, and phasic modulations by an important neurobiological system were integrated. The results show that cognitive-neurophysiological subprocesses during the actual switching processes, reflected by the N2 and P3 ERP components, are not modulated by the norepinephrine system. Rather, this system modulates preparatory processes in the fore period of stimuli signaling possible switches of response sets. The source localization results show that this is achieved by modulating neural processes in the temporo-parietal junction (BA40). Importantly, these phasic modulatory effects of the norepinephrine system were only evident when working memory processes had to be used to guide the selection of the appropriate responses for task switching.
Keywords: dospělí; reakční čas; Task switching; Humans; Attention; Reaction Time; noradrenalin; Young Adult; mladý dospělý; elektroencefalografie; kognice; mužské pohlaví; pozornost; mapování mozku; Evoked Potentials; evokované potenciály; Adult; Pupil diameter; temenní lalok; Memory; Electroencephalography; Norepinephrine; EEG; ženské pohlaví; Pupil; paměť; Working; Brain Mapping; Cognition; podněty; lidé; Source localization; pupila; Parietal cortex; Cues; Male; Parietal Lobe; Female